EU Integrated Maritime Policy and multilevel governance - Moreira, Fátima Castro (2020)
Marine and coastal environment are under pressure from several pollution sources. Most of the environmental law was developed on a sectoral basis and does not reflect the interdependence of the various issues and their solutions. Since the adoption of Blue Book, EU legislation to protect the marine environment has been progressively implemented in many relevant areas: Fisheries, Shipping, Tourism, energy, etc. The Integrated Maritime Policy covers several cross-cutting policies, more specifically blue growth, marine data and knowledge, maritime spatial planning, integrated maritime surveillance, and sea basin strategies. Oceans and sea are influenced by many activities, interests and policies and are interlinked. A holistic, integrated approach is the best way to handle maritime affairs, with States cooperation not only on an EU States basis but also with third States and International Organizations. International Organizations provide an essential forum for international cooperation in relation to environmental issues. In this context they have two important roles to play: environmental policy-making and the development of international environmental law.